Electron acceleration in a JET disruption simulation. (9th August 2018) - Sommariva, C.; Nardon, E.; Beyer, P.; Hoelzl, M.; Huijsmans, G.T.A.
Abstract: Runaways are suprathermal electrons having sufficiently high energy to be continuously accelerated up to tens of MeV by a driving electric field (Connor and Hastie 1975 Nucl. Fusion 15 415). Highly energetic runaway electron (RE) beams capable of damaging the tokamak first wall can be observed after a plasma disruption (Reux et al 2015 Nucl. Fusion 55 129501). Therefore, it is of primary importance to fully understand their generation mechanisms in order to design mitigation systems able to guarantee safe tokamak operations. In a previous work, Sommariva et al (2018 Nucl. Fusion 58 ), a test particle tracker was introduced in the JOREK 3D non-linear MHD code and used for studying the electron confinement during a simulated JET-like disruption. It was found in Sommariva et al (2018 Nucl. Fusion 58 ) that relativistic electrons are not completely deconfined by the stochastic magnetic field taking place during the disruption thermal quench (TQ). This is due to the reformation of closed magnetic surfaces at the beginning of the current quench (CQ). This result was obtained neglecting the inductive electric field in order to avoid the unrealistic particle acceleration which otherwise would have happened due to the absence of collision effects. The present paper extends (Sommariva et al 2018 Nucl. Fusion 58 ) analysing test electron dynamics in the same simulated JET-like disruption using the complete electric field. For doing so, a simplified collision model is introduced in the particle tracker guiding center equations. We show that electrons at thermal energies can become RE during or promptly after the TQ due to a combination of three phenomena: a first REs acceleration during the TQ due to the presence of a complex MHD-induced electric field, particle reconfinement caused by the fast reformation of closed magnetic surfaces after the TQ and a secondary acceleration induced by the CQ electric field.